Pengaruh Cara Pengeringan Dengan Oven, Kering Angin Dan Cahaya Matahari Langsung Terhadap Mutu Simplisia Herba Sambiloto - Rina Wahyuni; Guswandi Guswandi; Harrizul Rivai (Jurnal Farmasi Higea, 2014)
The influence of drying method to the quality of sambiloto’s herbal crude had been done. The drying methode that used are oven drying at 45o C, direct sunlight drying and wind drying. The results showed that oven drying gave the best result with drying shrinkage value of 9.1147%, 9.3339% total ash value, acid insoluble ash content of 0.7768%, the levels of water-soluble extract 19.3226% and levels of 17.5160% ethanol-soluble extract.